Pendukung Keputusan dalam Penilaian Pegawai Pemerintah Non Pegawai Negeri menggunakan Metode Entropy - Cintantya Andhita Dara Kirana; Anggi Syahadat Harahap (JURIKOM (Jurnal Riset Komputer), 2022)
Polytechnic of STIA LAN Bandung is one of the units under the LAN RI which has a core business in the field of education that has an obligation to run the Tri Dharma of Higher Education. In running the Tri Dharma of Higher Education, Polytechnic of STIA LAN Bandung requires several supporting resources. One of the supporting resources that most determine the quality of the implementation of the Tri Dharma of Higher Education is the competence of human resources. To facilitate the decision-making process carried out by the Staffing sub-section in assessing Non-Civil Servant Government Employees (PPNPN), a form of Decision Support System is needed. In conducting employee assessments used a method, namely Entropy. Entropy method that serves to measure the weight (level of importance) on each assessment indicator. Assessment indicators, which are used include Basic Values, Performance, Insight Tests, Warning Letters, and Attendance. The dataset used is secondary data that has been obtained from the staffing sub-section of Polytechnic of STIA LAN Bandung. The data sample consisted of five non-civil servants (PPNPN). From the results of the weight calculation using the Entropy method, it was obtained that the Attendance Indicator has the largest weight value of 0.5495, followed by the Warning Letter indicator with a weight of 0.2353. Then the third largest weight is on the Performance indicator with a weight of 0.1107, followed by the Basic Value indicator with a weight of 0.0604. The smallest weight gain is generated by the Insight Test indicator of 0.0439